Clinical outcome of SARS-CoV-2 infections occurring in multiple myeloma patients after vaccination and prophylaxis with tixagevimab/cilgavimab - Duminuco, Andrea; Romano, Alessandra; Leotta, Dario; La Spina, Enrico; Cambria, Daniela; Bulla, Anna; Del Fabro, Vittorio; Tibullo, Daniele; Giallongo, Cesarina; Palumbo, Giuseppe A.; Conticello, Concetta; Di Raimondo, Francesco (Frontiers in Oncology, 2023)
Patients with multiple myeloma (MM) frequently reported immune impairment with an increased risk for infection-related mortality. We aimed to evaluate the immune response in MM patients vaccinated for SARS-CoV-2 during active treatment. We enrolled 158 patients affected by active MM or smoldering MM (SMM) and 40 healthy subjects. All subjects received 2 or 3 doses of the BNT162b2 (Pfizer/BioNTech) vaccine, and the anti-spike IgG values were evaluated after every dose. At 30 days from the second dose, the median antibodies level in MM was 25.2 AU/mL, lower than in SMM and in the control group. The same results were confirmed after the third dose, with lower median anti-spike IgG levels in MM, compared to SMM and control group. We applied the Propensity Score Matching (PSM) as consequence of the limited sample size and its heterogeneity to adjust for differences in baseline clinical variables between MM patients who achieved or not a vaccine response after 2 or 3 doses. Following PSM, lack of response to SARS-CoV-2 complete vaccination plus boost was associated to age more than 70 years old and use of high-dose of steroids. We failed to identify an association between specific treatment types and reduced vaccine response. The use of prophylaxis with tixagevimab/cilgavimab for 40 non-responder patients after 3 doses of vaccine has proven to be an effective and safe approach in reducing the risk of serious illness in the event of a breakthrough SARS-CoV-2 infection, faced with a mild symptomatic course, and in providing protection instead of long-term humoral immune vaccine responses. Following PSM, only the high-risk cytogenetic abnormalities were associated to increased risk to develop a breakthrough SARS-CoV-2 infection.